Self-healing algorithm based on feedback mechanism - Ji-hong ZHAO; Hua QU; Wen-dong CHEN (Tongxin xuebao)
A network self-healing algorithm was presented.The proposed algorithm reduced the probability of selecting the failure or congestion paths and achieved self-healing by selecting recovery path adaptively when the nodes failure or link congestion in the network,which was based on Q-learning feedback mechanism,multi-QoS constrained of the evaluation function and path selection strategy using Boltzmann-Gibbs distribution.Simulation results show that the proposed algorithm outperforms in the recovery rate,the diffserv-aware capability and network resource optimization.